THE EFFECTIVENESS OF SUPPLEMENTARY FEEDING ON TODDLERS’ NUTRITIONAL STATUS IN REDUCING STUNTING IN RIVERBANK AREAS - Elsie Anggreni; Sri Wahyuni; Yola Alqorien Mustikarani (Adisam Publisher, 2026)
Stunting is a chronic nutritional problem that affects children’s physical growth and cognitive development. Supplementary feeding is one of the strategies implemented to improve toddlers’ nutritional status and reduce stunting prevalence. This study aimed to evaluate the effectiveness of supplementary feeding on toddlers’ nutritional status in riverbank areas. This study employed a pre-experimental design with a one-group pre–post test approach. The sample consisted of 40 toddlers aged 6–59 months who received supplementary feeding for 90 days. Anthropometric measurements were conducted to assess height-for-age, weight-for-age, and weight-for-height z-scores based on WHO standards. Data were analyzed using paired t-test and Wilcoxon test. The results showed a significant improvement in toddlers’ nutritional status after the intervention. The mean height-for-age z-score increased from -2.31 to -1.78 (p = 0.001). The prevalence of stunting decreased from 45.0% to 25.0%. Body weight and height also increased significantly after supplementary feeding. In conclusion, supplementary feeding is effective in improving toddlers’ nutritional status and reducing stunting prevalence in riverbank communities. These findings suggest that supplementary feeding programs should be implemented continuously and integrated with nutrition education and community-based interventions.